Man and Mangroves : How Far do they Go Hand in Hand? A Perspective with Respect to the Mangrove Ecosystems of Kerala State - Thomas, George; Radhakrishnan, Tresa (Indian Forester, 1999)
The interdependence of man and mangroves has changed to a great extent over time. Earlier, man had a healthy two-way association with mangroves, that is, man encouraged the growth and colonisation of mangroves, and mangroves, in their turn, provide firewood, timber, medicine, food etc. However, in recent times man has started overexploiting mangroves leading to their destruction. In Kerala, small stretches of mangroves available are to be considered as the relics of a glorious past when thousands of hectares of land was covered with mangrove vegetation. The major problems concerning the destruction of mangroves in Kerala are lack of awareness among public, injudicial tourism activities and pollution from industrial effluents. Thus, for the amelioration of the available mangrove habitats we need a better awareness among public, popularisation of eco-tourism and the imposition of regulatory measures on industrial pollution and waste discharge into the mangrove areas. Large scale afforestation programmes can also play a vital role in the conservation of these fragile ecosystems.